Synthesis of biolubricant by esterification of oleic acid and pelargonic acid with trimethylolpropane over tin(ii) oxide - Foo, Jia Huoy (2014)
Increasing demand of biolubricant nowadays due to the promotions replacement of non-renewable raw materials by renewable resources and minimisation of the environmental impact that caused by improper disposal issue. Current biolubricant production processes which involving the reaction of vegetable oil and alcohol with the presence of homogeneous catalyst causing the catalysts cannot be recycled, soap formation, high separation cost during the downstream of reactions and etc. To overcome these problems, researches were done by using solid catalysts. However, the research using heterogeneous catalyst, metal oxide is scarce. So, this paper presents the best operating condition for the synthesis of biolubricant through the esterification of oleic acid(OA) and pelargonic acid(PA) with trimethylolpropane(TMP). Fatty acid(FA) were reacted with TMP using different molar ratios and operating temperatures with the presence of tin(II) oxide under atmospheric pressure. The samples withdrawn were titrated for its total acid number (TAN). The reaction was proven not limited by both external and internal diffusions. The highest conversion of 80.49% was achieved at the molar ratio OA:TMP of 1:2.4 and operating temperature of 150°C. An identical conversion was achieved with lower FFA for the synthesis of biolubricant using PA. Trimethylolpropane tripelargonate(TMTP) with lower viscosity and FFA value would prevent corrosion and reduce friction in the engine. The fresh and used catalysts were characterized by Fourier transforms infrared spectroscopy (FTIR) and proven that tin(II) oxide can be reuse after the reaction. The initial rates and K values is determined. The findings of the present work are useful for the optimisation of the biolubricant production in future. The activation energy for the esterification were found to be 48.612 kJ/mol for the formation of TMTO and 52.303 kJ/mol for the formation of TMTP. The rate constant and equilibrium constant were found to be increased with temperature. The thermodynamic properties of the reaction OA with TMP were found to be Gibbs free energy, ΔG=-82.159kJ/mol, enthalpy, ΔH=- 81.9511kJ/mol and entropy ΔS=0.208 kJ/mol. The thermodynamic properties of the reaction PA with TMP were found to be ΔG=-71.357kJ/mol, ΔH=- 71.176kJ/mol and entropy ΔS=0.181 kJ/mol